Trans-Diaquabis(cyclohexane-1,2-diamine)zinc(II) dichloride - Karimnejad, K.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
In the title compound, [Zn(C6H14N2)(2)(H2O)(2)]Cl-2, the Zn(II) atom resides on a special position with site symmetry 2/m and is octahedrally coordinated by four N atoms from two trans 1,2-diaminocyclohexane ligands and two water O atoms. In the crystal, N-H...Cl and O-H...Cl hydrogen bonds link the molecules into a two-dimensional network parallel to the bc plane.